HUBUNGAN ANTARA PENDAPATAN DAN KARAKTERISTIK PARA PELAKU EKONOMI LAMPU MERAH DI JAKARTA - Tiara Puspa; Catur Rahayu Martiningyas; Wiwik Robiatul Adawiyah (Universitas Trisakti, 2005)
This research discovers correlation between income and the characteristic of the Lampu Merah (Traffic Light) traders and beggars. The 154 respondents which are spreading at the intersecion in Jakarta. The result shows that there is correlation between the characteristic of trader and beggar and income.